Facile synthesis of silver-tin oxide electrical contact materials by in-situ decomposition of a uniform mixture precursor. Issue 1 (November 2015) - Lin, Z J; Sun, X D; Liu, S H; Xie, M; Chen, J L; Li, J G
Abstract: A uniform mixture precursor containing Ag2 O and Ag2 SnO3 was synthesized via a facile ion exchange reaction method. The influence of pH value on composition and precipitation rate of the precursor was investigated systematically. The Ag-SnO2 composite powder was obtained by decomposition of the precursor at 600°C, and uniform mixing of elements was inherited from the precursor and fresh and intimate Ag-SnO2 interfaces were created. The Ag-SnO2 electrical contact material was prepared using this composite powder by hot-pressing method. It was found that nano-sized SnO2 particles (about 20.6 nm) are homogeneously dispersed in the Ag-matrix. The as-prepared Ag-SnO2 electrical contact material shows excellent performances, such as high hardness (154 MPa), high density (9.90 g/cm 3 ) and good electrical conductivity (72.24%IACS).